Optimasi Transisi dari Pendidikan Anak Usia Dini (PAUD) ke Sekolah Dasar: Membangun Kesiapan Siap Sekolah melalui Tinjauan Literatur - Nurdianah, Andi; Suarni, Suarni; Kasim, Kasim; Nasir, Nasir (Journal of Leadership, Management and Policy in Education, 2024)
This research aims to optimize the transition from Early Childhood Education (ECE) to Primary School (PS) by building school readiness. Utilizing an analysis of relevant articles published between 2020-2024 from Google Scholar with the keyword "Transition ECE-PS," this research explores factors supporting children's readiness for this transition phase. The research method involves examining the role of teachers, the utilization of technology, the involvement of parents, and the psychological aspects of children as crucial elements in fostering this readiness. Through understanding the findings from various studies, this research provides foundation for educational stakeholders to enhance the effectiveness of ECE-PS transition programs. In conclusion, comprehensive and evidence-based strategies are needed to create a positive transition experience for children in their early education stages.